(untitled) (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
Mithraism, like other cults, sought to elucidate the origins of the Universe. In this context, The Cosmos is forged through symbolic imagery in the Mithraic iconography. Given the paucity of textual sources by initiates, scholars interpreted the myth through Mithraic imagery. The central iconographical representation of the cult, the tauroctony, displays the sacrifice of the bull by Mithras and each zoomorphic and anthropomorphic motif that frames the sacrifice carries an astral signification. This paper examines regional adaptations of the tauroctony, particularly from Dacia, focusing on their deviations from the Roman canon of representations. In this regard, the Dacian additional motifs indicate the reconstruction of the myth inside the territory.